Pertumbuhan Gulma Padi Sawah pada Berbagai Takaran Alelokimia Kulit Buah Jengkol [Pithecellobium Jiringa (Jack) Prain Ex King] - Nurjanah, Uswatun; Yudono, P.; Suyono, A.T; Shieddiq, Dja’far (Akta Agrosia, 2015)
Jiringa hulls contained phenolic compound, alcaloide, steroide, and flavonoide. Phenolic compound could inhibit the growth of emergence of rice. This study was aimed evaluate effect of dosage jiringa hulls application in supressing weed growth and promoting rice growth and yield. The treatment were weed free, weedy, hand weeding at 21 and 42 dap, jeringa hulls application of 5, 10, and 15 ton ha-1. Result showed that jeringa hulls aplication of 10 and 15 ton ha-1 can subtituted hand weeding at 21 and 42 dap and can suppresed broad leafed and narrow leafed weed at 6 and 9 wap compared to weedy, respectively. Highest suppressed as 90% if jiringa hulls was aplication at 15 ton ha-1.